THE REALTIONSHIP BETWEEN FAMILY SUPPORT WITH NEGLECT OF THE ELDERLY - Khalisah Amalia; Anung Ahadi Pradana (Jurnal Mitra Kesehatan, 2024)
Introduction : The elderly are the final stage in the development of life and cannot be avoided by individuals. As time goes by, life expetancy increases, and neglect of the elderly will occur. Purpose: the research aims to determine the picture of neglect of elderly anda the relationship between family support and neglect of the eldelry in Mangunjaya Village Method: This research design uses a cross sectional design carried out in June 2023 in Mangunjaya Village. The total sample obtained was 110 people based on the Slovin formula, with the inclusion criteria being elderly aged more than 60 years, living with family or having a family, elderly people able to understand questionnaire questions (reading or interviews), and living or residing in the Mangunjaya Village area. The instrument used in this research was the family support and neglect questionnaire. This research uses a quantitative design with a cross-sectional approach.Result: Statistical test result using chi-square with a confidence interval of 90% and lamda=0,05. The result of the data analysis showed a significat relationship between family support and neglect of the elderly, with a p-value=0,000 < lamda (0,05) Conclusion: The research results show that there is a relationship between family support and family neglect. The elderly need support from their families so they can avoid incidents of neglect in the family.